2019
DOI: 10.3390/met9101084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zr, Y on the Microstructure and Properties of As-Cast Cu-0.5Y-xZr (wt.%) Alloys

Abstract: In this paper, the microstructure and properties of as-cast Cu-Y-Zr alloys with different Zr content were studied in order to investigate whether the precipitates in copper alloys would interact with each other by adding Y and Zr simultaneously. As-cast Cu-0.5Y-xZr (wt.%, x = 0.05 and 0.1, nominal composition) alloys were prepared by vacuum melting in this study. Scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), and transmission electron microscopy (TEM) were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In addition, under the same conditions, the average orientation φ of Cu–Ni–Co–Si–Cr–Ce (11°) is lower than that of Cu–Ni–Co–Si–Cr (16°) [ 13 ]. Liang et al studied the effects of Y and Zr addition on the microstructure and properties of as-cast Cu–Y–Zr alloy [ 14 ]. The results show that, due to the low solid-solubility of Y and Zr in Cu, the amount of precipitated Cu 5 Y and Cu 5 Zr phases increased by adding Y to refine the grains, and thus solid-solution enhancement of Cu–0.5Y–xZr alloy is realized [ 14 ].…”
Section: Influence Mechanismmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, under the same conditions, the average orientation φ of Cu–Ni–Co–Si–Cr–Ce (11°) is lower than that of Cu–Ni–Co–Si–Cr (16°) [ 13 ]. Liang et al studied the effects of Y and Zr addition on the microstructure and properties of as-cast Cu–Y–Zr alloy [ 14 ]. The results show that, due to the low solid-solubility of Y and Zr in Cu, the amount of precipitated Cu 5 Y and Cu 5 Zr phases increased by adding Y to refine the grains, and thus solid-solution enhancement of Cu–0.5Y–xZr alloy is realized [ 14 ].…”
Section: Influence Mechanismmentioning
confidence: 99%
“…Liang et al studied the effects of Y and Zr addition on the microstructure and properties of as-cast Cu–Y–Zr alloy [ 14 ]. The results show that, due to the low solid-solubility of Y and Zr in Cu, the amount of precipitated Cu 5 Y and Cu 5 Zr phases increased by adding Y to refine the grains, and thus solid-solution enhancement of Cu–0.5Y–xZr alloy is realized [ 14 ]. Saha et al found that adding elemental Sc to Cu–Zn–Al shape-memory alloy can reduce the phase-transition temperature and thus improve the mobility of the martensite/austenite interface [ 32 ].…”
Section: Influence Mechanismmentioning
confidence: 99%
See 3 more Smart Citations